G275 Children and Young People's Views on Research Without Prior Consent in Life Threatening Situations: A Qualitative Study. (24th May 2017) - Roper, L; Sherratt, F; Young, B; McNamara, P; ,; Appleton, R; Crawley, E; Dawson, A; Frith, L; Gamble, C; Woolfall, K
Abstract : Aims: Variations from informed consent (known as deferred consent or research without prior consent-RWPC) enable paediatric critical care research to proceed by allowing consent to be sought after a child has received an investigational intervention. The first UK trials conducted in this setting show high levels of recruitment, yet children and young people (CYP) were rarely involved in recruitment discussions, often because they were too young or too poorly. We aimed to explore CYP's views on RWPC and identify methods of involving them in decisions about their participation in critical care research. Methods: Qualitative interview study involving 14 CYP (aged 7 to 15 years) with chronic health conditions and experience of paediatric emergency care treatment in the 12 months prior to interview. Results: CYP were keen to be included in critical care research without prior consent if doctors viewed the trial intervention to be safe and of potential benefit to participants and others. All CYP felt that they have the right to be informed and have a say about their participation in a trial as soon as they had recovered. CYP suggest methods to help practitioners and parents facilitate RWPC discussions with children, including videos, cartoons, websites and leaflets. Conclusion: CYP support research without prior consent in life threatening situations and provide examples of how multimedia resources could be used to engage and involve children in decisions about participation in research when they have recovered.